2017
DOI: 10.1017/jns.2017.9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of changing the moisture levels of dry extruded and wet canned diets on physical activity in cats

Abstract: Obesity levels in cats are increasing and the main causative factor is higher energy intake v. energy expenditure over time. Therefore, altering energy expenditure by enhancing physical activity of the cat could be a strategy to reduce obesity. Hydrating commercial dry diets with water increased activity in cats; however, no study has compared this approach with feeding high-moisture canned diets. Eight healthy male neutered domestic shorthair cats were fed four different dietary treatments in a Latin square d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
8
1
Order By: Relevance
“…Interestingly, some studies have indicated that increased water content promotes physical activity (Deng et al, 2014 ). However, this finding was not replicated in our colony (Thomas et al, 2017 ). While obesity has been observed in young, growing cats (Häring et al, 2013 ), it may be possible that the cats in the current study may develop changes in body composition as they continue to age.…”
Section: Discussioncontrasting
confidence: 70%
“…Interestingly, some studies have indicated that increased water content promotes physical activity (Deng et al, 2014 ). However, this finding was not replicated in our colony (Thomas et al, 2017 ). While obesity has been observed in young, growing cats (Häring et al, 2013 ), it may be possible that the cats in the current study may develop changes in body composition as they continue to age.…”
Section: Discussioncontrasting
confidence: 70%
“…No differences regarding sex were observed, and the obtained values were in accordance with a previous study using 2 H and cats fed dry diets, which reported 57 ml/kg 0•67 per d (11) . Several factors, however, may interfere in water turnover, and the obtained results cannot be generalised (59,60) . Therefore, evaluating high-moisture foods (>80 %) by the 3 H method, a water flux of 126 ml/kg 0•67 per d was reported (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Due to the physiological peculiarities of cats regarding water balance, it has been described that dry food intake results in the production of low volume and concentrated urine, as cats may not fully compensate for the low water intake from food by drinking more water (Anderson, 1982;Wellman, Dibartola, & Kohn, 2012). When fed dry diets, the total water intake of cats might be 29% to 63% lower compared with the water intake from the consumption of wet foods (cans and pouches), and the water balance may be maintained by the reduction in renal water excretion (Anderson, 1982;Buckley, Hawthorne, Colyer, & Stevenson, 2011;Carciofi, Bazolli, Zanni, Kihara, & Prada, 2005;Thomas, Post, & Bosch, 2017). This physiological response has been suggested as a possible risk factor for the development of the clinical presentations of lower urinary tract diseases in cats (Buffington et al, 1997;Lekcharoensuk et al, 2001;Walker et al, 1977).…”
Section: Introductionmentioning
confidence: 99%